Hubungan Social Comparison dengan Self Esteem pada Mahasiswa Pengguna Media Sosial TikTok di Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember - Lailatul Fitri; Indah Roziah Cholilah (Fakultas Dakwah UIN KHAS Jember, 2024)
The purpose of this study was to test and determine whether there is a relationship between social comparison and self esteem in students who use TikTok social media at the Faculty of Da'wah, Kiai Haji Achmad Siddiq Jember State Islamic University. The approach used in this research is a quantitative approach that focuses on correlation. The sample collection method in this study used purposive sampling technique with the number of respondents 205 students of class 2022 of the Faculty of Da'wah. Data were collected through questionnaires and analyzed using pearson product moment techniques. The results of the pearson product moment analysis technique show a significance value of 0.000 with a comparison of the hypothesis test guideline value <0.05, therefore the two variables of social comparison with self esteem are stated to be related, because Ha is accepted and H0 is rejected. The Pearson Correlation value of -0.247 indicates a negative relationship between social comparison and self esteem. This result shows that the lower the social comparison, the higher the sellf elstelm. Conversely, the higher the social comparison, the lower the self esteem.